Association between Torso Gunshot Wound Volumes of Trauma Centers and Outcomes of Torso Gunshot Wound Patients. A Propensity-Matched Nationwide Cohort Study. (2nd November 2021) - Fu, Chih-Yuan; Bajani, Francesco; Bokhari, Marissa; Butler, Caroline; Starr, Frederick; Messer, Thomas; Kaminsky, Matthew; Dennis, Andrew; Schlanser, Victoria; Poulakidas, Stathis; Mis, Justin; Bokhari, Faran
Abstract: Objective : The number and type of patients treated by trauma centers can vary widely because of a number of factors. There might be trauma centers with a high volume of torso GSWs that are not designated as high-level trauma centers. We proposed that, for torso gunshot wounds (GSWs), the treating hospital's trauma volume and not its trauma center level designation drives patient prognosis. Methods: The National Trauma Data Bank was queried for torso GSWs. The characteristics of torso GSWs in trauma centers with different volumes of torso GSWs were compared. The association between torso GSW volumes of trauma centers and the outcomes of torso GSWs were evaluated with propensity score matching (PSM) and multivariate logistic regression (MLR) analysis. Results: There were 618 trauma centers that treated 14, 804 torso GSW patients in two years (2014-2015). In 191 level I trauma centers, 82 of them (42.9%, 82/191) treated <1 torso GSW per month. After well-balanced PSM, patients who were treated in higher volume trauma centers (≥9 torso GSWs/month) had a significantly lower mortality rate (7.9% vs. 9.7%). Patients treated in trauma centers with ≥9 torso GSWs/month had a 30.9% (odds ratio = 0.764) lower probability of death than if sent to trauma centers with <9 torso GSWs/month. Treatment in level I or II trauma centers did not significantly affect mortality. Conclusion: There is an uneven distribution of torso GSWs among trauma centers. Torso GSWs treated in trauma centers with ≥9 torso GSWs/month have significantly superior outcomes with regard to survival.